MOST work measurement systems - Zandin, Kjell B. (Industrial engineering (Marcel Dekker, Inc.), 1990)
In 1972 a new system of measuring work was introduced that rivaled the developments of other work measurement pioneers such as Taylor, Gilbreth, Gantt, and Maynard. Most Work Measurement Systems, Second Edition describes this revolutionary technique, which is designed to simplify and speed up the process of setting engineered time standards.